2009
DOI: 10.3917/cca.151.0199
|View full text |Cite
|
Sign up to set email alerts
|

Honoraires d'audit et comités d'audit : le cas de la France

Abstract: Distribution électronique Cairn.info pour Association Francophone de Comptabilité. © Association Francophone de Comptabilité. Tous droits réservés pour tous pays.La reproduction ou représentation de cet article, notamment par photocopie, n'est autorisée que dans les limites des conditions générales d'utilisation du site ou, le cas échéant, des conditions générales de la licence souscrite par votre établissement. Toute autre reproduction ou représentation, en tout ou partie, sous quelque forme et de quelque man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 32 publications
2
9
0
4
Order By: Relevance
“…According to Table 2, Panel A average audit fees are 5.09 M€ (median: 1.30) over the period (2006)(2007)(2008). This average amount is consistent with previous literature (mean: 4.45 M€ (median: 1.38 M€) for Gonthier-Besacier and Schatt (2007) on the SBF 250 index in 2002, and mean: 4.8 M€ for Broye (2009) on the Eurolist in 2005). We observe a wide diversity with a minimum of 0.02 M€ and a maximum of 52.50 M€.…”
Section: Data Collectionsupporting
confidence: 92%
“…According to Table 2, Panel A average audit fees are 5.09 M€ (median: 1.30) over the period (2006)(2007)(2008). This average amount is consistent with previous literature (mean: 4.45 M€ (median: 1.38 M€) for Gonthier-Besacier and Schatt (2007) on the SBF 250 index in 2002, and mean: 4.8 M€ for Broye (2009) on the Eurolist in 2005). We observe a wide diversity with a minimum of 0.02 M€ and a maximum of 52.50 M€.…”
Section: Data Collectionsupporting
confidence: 92%
“…In her major study, Broye (2009) claims that a positive association between the existence of an audit' committee and audit fees' level. Previous studies have reported a positive and significant association between audit committee independence and audit fees' level (Abbott, Parker, Peters, & Raghunandan, 2003;Chen, Duh, & Shiue, 2008;Goodwin-Stewart & Kent, 2006).…”
Section: Corporate Governance and Audit Qualitymentioning
confidence: 99%
“…A possible reason for this result may relates to the complementary effect between the internal and the external audit as two governance mechanisms (Goodwin‐Stewart and Kent, ). The positive variability of the IAFHELP's variable highlights that a corporate demand has the effect of limiting agency costs that result from conflicts of interest between shareholders and managers (Broye, ). Consistent with Panel B Exhibit , the highest correlation is equal to 0.5578.…”
Section: Resultsmentioning
confidence: 99%
“…The internal auditor contributes to the audit of financial statements as an assistant who works under the direct supervision of the external auditor. When the internal auditor is significantly involved in strengthening the internal control, the external auditor reliance on the client's internal control will increase and the external auditor's fees decrease (AICPA, 1997;Broye, 2009;Felix et al, 2001;PCAOB, 2010). Felix et al (2001) found that the external auditor's confidence on the IA work is influenced by his perception of the quality of the IAF as well as, conditioned by the level of inherent risk.…”
Section: Quality Of the Iafmentioning
confidence: 99%